PENGARUH KEPERCAYAAN DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KPP PRATAMA JAKARTA GAMBIR DUA TAHUN 2023 - Mayada, Fadhlika; Rahmi, Notika (Jurnal Ilmu Administrasi Publik, 2025)
Individual Taxpayer Compliance at KPP Pratama Jakarta Gambir Dua in reporting SPT in 2023 has decreased as proven by data obtained from KPP Pratama Jakarta Gambir Dua which shows the number of Individual Taxpayers namely 8,076 while the actual reporting of SPT for Individual Taxpayers is only 7,592. This decrease in taxpayer compliance has resulted in a decrease in state revenues from tax sector at KPP Pratama Jakarta Gambir Dua. One of the factors that causes a decrease in individual taxpayer compliance in this research is trust and tax sanctions. This research aims to analyze the influence of Trust and Tax Sanctions on Individual Taxpayer Compliance at KPP Pratama Jakarta Gambir Dua in 2023. This research uses a quantitative approach. The sampling technique in this research was carried out using simple random sampling with a total of 100 individual taxpayers registered at KPP Pratama Jakarta Gambir Dua. The data was processed using SPSS Version 26, to determine the magnitude of the influence the researchers used the F test, t test, and coefficient of determination. The research results show that there is a positive and significant influence of Trust on Individual Taxpayer Compliance of 12,6%. There is a positive and significant influence of Tax Sanctions on Individual Taxpayer Compliance of 44,6%. Trust and Tax Sanctions simultaneously have a positive and significant effect on Individual Taxpayer   Compliance   at   KPP   Pratama   Jakarta   Gambir   Duaamounting to 46,3%.